THE REPRESENTATION OF MIGRANTS IN AUSTRALIAN DETECTIVE FICTION - Phillips, Bill (2014)
This articles analyses the nexus between crime and migration in the Australian crime novel phenomenon focussing principally on the authors Peter Temple, Shane Maloney, Philip McLaren and Peter Corris. Fiction, which both helps to reflect and to construct our world, provides us with a vision and a version of contemporary Australian. The questions which arise from these novels are: What does it mean to be Australian? Immigrant? Foreigner? What links are there between crime novel and place? Does crime fiction hold up a mirror to society? What role do ethnic groups play in organised crime? Is organised crime involved in the exploitation of immigrants and in illegal immigration? How is the Aboriginal community represented and what role does it play in Australian crime fiction? Reference works which shine a light on true crime in Australia and its links to migration and immigrants include Blood Brothers by Bertil Lintner, Gangland Australia by James Moton and Suzanna Lobez, Leadbelly by John Silvester and Andrew Rule and Gangland Crimes that Shocked Australia by Ian Ferguson